2005
DOI: 10.1158/1078-0432.ccr-04-2283
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of the Intratumoral Administration of Recombinant Canarypox Viruses Expressing B7.1 and Interleukin 12 in Patients with Metastatic Melanoma

Abstract: The objective of this study was to evaluate the safety and activity of the intratumoral administration of the immune costimulatory molecule, B7.1, encoded by a vector derived from the canarypox virus, ALVAC (ALVAC-B7.1), alone and with the intratumoral injection of ALVAC encoding the immune-stimulatory cytokine, interleukin 12 (ALVAC-IL-12). Fourteen patients with metastatic melanoma who had s.c. nodules received intratumoral injections on days 1, 4, 8, and 11. Nine patients were given escalating doses of up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…However, the modest antitumoral responses mediated by vectors tested in clinical trials questions the translation of preclinical results (Sangro et al, 2004;Triozzi et al, 2005;Mahvi et al, 2007;Daud et al, 2008). We think that direct comparisons between available vectors in clinically relevant tumor models may enhance the success of gene therapy vectors in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…However, the modest antitumoral responses mediated by vectors tested in clinical trials questions the translation of preclinical results (Sangro et al, 2004;Triozzi et al, 2005;Mahvi et al, 2007;Daud et al, 2008). We think that direct comparisons between available vectors in clinically relevant tumor models may enhance the success of gene therapy vectors in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…First, it was reported that patients treated with IL-12 administered s.c. showed less severe side effects as compared to i.v. treated patients [26]; next, novel forms of IL-12 non-viral delivery such as alum, liposome and polymer-based delivery have shown in pre-clinical models promising effects and significantly reduced systemic toxicity [27][28][29]. Taken together, a clinical trial in AML patients appears to be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Transfer of cytokine genes is thereby a possible strategy for cancer treatment and is currently being investigated for its clinical feasibility (Chiyo et al, 2004;Triozzi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%